La informalidad en el empleo y el ingreso proveniente del trabajo en Loreto periodo 2016 - 2020 - Flores Urrelo, Ana Lucía (2023)
The main source of income for people is work, which can be developed formally and informally. Obviously, the worker with informal employment will face the risk of seeing their salary and labor rights violated. This magisterial thesis aims to determine the relationship between informality in employment and income from work in Loreto, in the period 2016 - 2020. Oriented by this purpose, this Quantitative, Correlational and design study is carried out Not experimental. The conclusions reached is that it is demonstrated that there is no relationship between informality in employment and income from work in Loreto, in the period 2016 - 2020; since in the statistical test values far from the minimum accepted standards were reached, with the Correlation Coefficient being r = -0.413824833; and the Coefficient of Determination R2 = 0.171250992. On the other hand, the employed population was made up mainly of people with informal employment at 81.70%, and to a lesser extent the population with formal employment, which represented 19.30%. On the other hand, the analysis of the sex of the workers with informal employment shows that the majority was made up of the female sex, meaning 74.93%, while those of the male sex represented 25.07%. The average income from work in Loreto was lower than the national one (-S/. 210.36).